Clinical outcomes with β-blockers for myocardial infarction: a meta-analysis of randomized trials - Bangalore, Sripal; Makani, Harikrishna; Radford, Martha; Thakur, Kamia; Toklu, Bora; Katz, Stuart D; DiNicolantonio, James J; Devereaux, P J; Alexander, Karen P; Wetterslev, Jorn; Messerli, Franz H (The American journal of medicine, 2014)
Debate exists about the efficacy of β-blockers in myocardial infarction and their required duration of usage in contemporary practice. We conducted a MEDLINE/EMBASE/CENTRAL search for randomized trials evaluating β-blockers in myocardial infarction enrolling at least 100 patients. The primary outcome was all-cause mortality. Analysis was performed stratifying trials into reperfusion-era (> 50% undergoing reperfusion or receiving aspirin/statin) or pre-reperfusion-era trials. Sixty trials with 102,003 patients satisfied the inclusion criteria. In the acute myocardial infarction trials, a significant interaction (Pinteraction = .02) was noted such that β-blockers reduced mortality in the pre-reperfusion (incident rate ratio [IRR] 0.86; 95% confidence interval [CI], 0.79-0.94) but not in the reperfusion era (IRR 0.98; 95% CI, 0.92-1.05). In the pre-reperfusion era, β-blockers reduced cardiovascular mortality (IRR 0.87; 95% CI, 0.78-0.98), myocardial infarction (IRR 0.78; 95% CI, 0.62-0.97), and angina (IRR 0.88; 95% CI, 0.82-0.95), with no difference for other outcomes. In the reperfusion era, β-blockers reduced myocardial infarction (IRR 0.72; 95% CI, 0.62-0.83) (number needed to treat to benefit [NNTB] = 209) and angina (IRR 0.80; 95% CI, 0.65-0.98) (NNTB = 26) at the expense of increase in heart failure (IRR 1.10; 95% CI, 1.05-1.16) (number needed to treat to harm [NNTH] = 79), cardiogenic shock (IRR 1.29; 95% CI, 1.18-1.41) (NNTH = 90), and drug discontinuation (IRR 1.64; 95% CI, 1.55-1.73), with no benefit for other outcomes. Benefits for recurrent myocardial infarction and angina in the reperfusion era appeared to be short term (30 days). In contemporary practice of treatment of myocardial infarction, β-blockers have no mortality benefit but reduce recurrent myocardial infarction and angina (short-term) at the expense of increase in heart failure, cardiogenic shock, and drug discontinuation. The guideline authors should reconsider the strength of recommendations for β-blockers post myocardial infarction.